Reconsolidation-Extinction Interactions in Fear Memory Attenuation: The Role of Inter-Trial Interval Variability - Auchter, Allison; Cormack, Lawrence K.; Niv, Yael; Gonzalez-Lima, Francisco; Monfils, Marie H. (Frontiers in Behavioral Neuroscience, 2017)
Fear extinction typically results in the formation of a new inhibitory memory that suppresses the original conditioned response. Evidence also suggests that extinction training during a retrieval-induced labile period results in integration of the extinction memory into the original fear memory, rendering the fear memory less susceptible to reinstatement. Here we investigated the parameters by which the retrieval-extinction paradigm was most effective in memory updating. Specifically, we manipulated the inter-trial intervals between conditional stimulus (CS) presentations during extinction, examining how having interval lengths with different degrees of variability affected the strength of memory updating. We showed that randomizing the inter-trial interval of CS presentations during extinction led to less return of fear via reinstatement than extinction with a fixed inter-trial interval. Subjects who received variable inter-trial intervals during extinction also showed higher freezing during the inter-trial interval, indicating that the randomization of CS presentations led to a higher general reactivity during extinction, which may be one potential mechanism for memory updating.